1995
DOI: 10.1001/archinte.1995.00430120054007
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Resuscitation in Intensive Care Unit and Non—Intensive Care Unit Patients

Abstract: Futile resuscitative efforts are routinely performed in part because physicians and patients are unaware of outcome results and factors that influence survival. A wider recognition of the limitations of cardiopulmonary resuscitation should lead to advanced directives that reflect this awareness, with substantially more patients choosing not to have cardiopulmonary resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…The successful CPR rate in other studies are as follow: 28.1% in Kermanshah (Saifi et al, 2010b), 29.3% in Shohadaye Haftom Tir, Tehran , 28.4% in selected educational centers of Tehran (Salari & Mohammadnejad, 2010), 19.9% in educational centers of Kashan (Ebell et al, 1998), 32% in Social Security emergency hospitals of Alborz Province (Nasiripour, Masoudi, & Fathi, 2012), 39.7% in Brazil (Moretti et al, 2007), 10.6% in Kermanshah (Goodarzi et al, 2015). One study showed that in critical ward, the rate of successful CPR was 3.3% (Jaberi, Changizian, & Mazlomzadeh, 2011;Karetzky, Zubair, & Parikh, 1995) and in other ward, this rate vary from 13% to 33% (Abella et al, 2005;Brindley et al, 2002;Taffet, Teasdale, & Luchi, 1988), also the successful CPR reported from 8% to 16% in some other studies (Karetzky et al, 1995). In Goodarzis study which was conducted in hospital, The ultimate success rate of resuscitation was 10.6%, and at six-month follow-up survey data on patients after discharge, the long-term success rate of the resuscitation was as 8.87% (Goodarzi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The successful CPR rate in other studies are as follow: 28.1% in Kermanshah (Saifi et al, 2010b), 29.3% in Shohadaye Haftom Tir, Tehran , 28.4% in selected educational centers of Tehran (Salari & Mohammadnejad, 2010), 19.9% in educational centers of Kashan (Ebell et al, 1998), 32% in Social Security emergency hospitals of Alborz Province (Nasiripour, Masoudi, & Fathi, 2012), 39.7% in Brazil (Moretti et al, 2007), 10.6% in Kermanshah (Goodarzi et al, 2015). One study showed that in critical ward, the rate of successful CPR was 3.3% (Jaberi, Changizian, & Mazlomzadeh, 2011;Karetzky, Zubair, & Parikh, 1995) and in other ward, this rate vary from 13% to 33% (Abella et al, 2005;Brindley et al, 2002;Taffet, Teasdale, & Luchi, 1988), also the successful CPR reported from 8% to 16% in some other studies (Karetzky et al, 1995). In Goodarzis study which was conducted in hospital, The ultimate success rate of resuscitation was 10.6%, and at six-month follow-up survey data on patients after discharge, the long-term success rate of the resuscitation was as 8.87% (Goodarzi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who had CPA and received CPR despite pressors were half as likely to survive hospitalization and less likely to have favorable neurological outcomes (3.3 vs. 7.0%). In many hospitals, CPR is provided to critically ill patients, including those in shock, often without patients' consent and based on small case series (3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Small single-center studies of CPR in the critically ill have demonstrated survival rates ranging from 0 to 47% (4)(5)(6)(7)(8)(9)(10). We hypothesized that patients who experience CPA despite administration of medications used to treat hypotension (pressors) are highly unlikely to respond to CPR.…”
mentioning
confidence: 99%
“…Yet the mortality rate range reflected in various studies does not consider survival following CPR in the ICU. In one recent study, only 3% of ICU patients survived the procedure (Karetzky, Zubair, & Parikh, 1995).…”
Section: Background: Elderly Patients and Hospital Deathsmentioning
confidence: 98%